PENGEMBANGAN MODEL SIMULASI RANTAI PASOK DARAH PMI KOTA YOGYAKARTA DI RS DR. SOERADJI TIRTONEGORO - WIBISONO S., ADITYIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main problem in the blood supply chain is inability of blood manager which is Red Cross or Blood banks, provide blood product according the demand. Demand for blood products in recent times tend to increase while the blood supply has not able to compensate for the condition. On the other hand is still very difficult for Red Cross or Blood banks to increase the amount of blood supply, due to health element that difficult in maintaining or improving the quality of the donor. This problem more difficult because of high complexity in the system as demand of blood product and blood bags supply that are stochastic, and the characteristic perishable on each product. This study aims to develop simulation model use Discrete Event Simulation (DES), which aims to evaluate and improve the blood supply chain performance, with the scope of study is located in Yogyakarta Regional Red Cross and Dr. Soeradji Tirtonegoro Hospital Blood Banks. The data used include the supply of blood bags, demand of blood product, and the production of blood products in Yogyakarta Regional Red Cross, as well as the amount of supply, demand and delivery of blood products in BDRS Dr. Soeradji Tirtonegoro. There are 3 models are constructed, namely sub-model of PMI Yogyakarta, submodels BDRS Dr. Soeradji Tirtonegoro, and the integration model of PMI Yogyakarta - BDRS Dr. Soeradji Tirtonegoro. The results of the supply chain simulation generates values for each supply chain performance 16% shortage of submodels for PMI Yogyakarta, 17% shortage for sub-models BDRS Dr. Soeradji Tirtonegoro, and 13% shortage for the integration model PMI Yogyakarta - BDRS Dr. Soeradji Tirtonegoro. Then several scenario are developed, consist of (1) percentage change in product production, (2) decrease in the number of blood bags reject, and (3) increase the amount of demand PRC from BDRS Dr. Soeardji Tirtonegoro to PMI Kota Yogyakarta for 24%. The combination of the scenario (1) and (2) give the increasing blood supply chain performance significantly for PMI Kota Yogyakarta, and scenario (3) give the increasing performance significantly for BDRS Dr. Soeradji Tirtonegoro. In addition, use sensitivity analysis on the parameter of modelling, it's found that the changes in the value of the amount of demand for blood product is the most sensitive parameters provide performance change in the system Keywords: discrete event simulation, blood supply chain, scenario development, sensitivity analysis